2001
DOI: 10.1542/peds.107.6.1309
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in Children Receiving Continuous Venovenous Hemofiltration

Abstract: The pattern of early multiorgan system failure and death, minimal relative cost of CVVH/D provision, and potential for improved outcome with initiation of CVVH/D at lesser degrees of fluid overload are factors that may support early initiation of CVVH/D in critically ill children with acute renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
371
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 502 publications
(387 citation statements)
references
References 11 publications
9
371
3
4
Order By: Relevance
“…Access was via internal jugular 6.5-French (Fr) hemodialysis catheters. Mean filter life was 51.1 h. Similar to other studies in pediatric CRRT patients [2-4, 5], fluid overload (FO), defined by the percentage weight gain over weight at admission to the neonatal intensive care unit (NICU), was independently associated with mortality [6]. Neonatal studies have reported an FO of >15-20 % to be associated with poor outcome defined as need for CRRT, prolonged NICU stay, time to extubation or death within 30 days postcardiothoracic surgery [7,8].…”
supporting
confidence: 72%
“…Access was via internal jugular 6.5-French (Fr) hemodialysis catheters. Mean filter life was 51.1 h. Similar to other studies in pediatric CRRT patients [2-4, 5], fluid overload (FO), defined by the percentage weight gain over weight at admission to the neonatal intensive care unit (NICU), was independently associated with mortality [6]. Neonatal studies have reported an FO of >15-20 % to be associated with poor outcome defined as need for CRRT, prolonged NICU stay, time to extubation or death within 30 days postcardiothoracic surgery [7,8].…”
supporting
confidence: 72%
“…28,29 Numerous observational studies of pediatric patients demonstrated fluid overload was associated with higher mortality. [30][31][32][33] In these studies, fluid overload >10% was associated with higher mortality when controlling for severity of illness. Data from the Prospective Pediatric CRRT Registry Group demonstrated again that % fluid overload was associated with mortality, and that survival was improved (76%) if dry weight was attained during CRRT as compared to those who did not attain dry weight (36%).…”
Section: Indicationsmentioning
confidence: 87%
“…Pediatricians have been at the forefront of identifying fluid overload as a risk factor for mortality in critically ill patients. 80 This is highlighted by the findings of the prospective pediatric continuous renal replacement therapy (CRRT) registry. Sutherland et al 81 showed in a prospective registry of 227 children who were on CRRT that those with a percentage fluid overload ,20% at initiation of renal replacement therapy had improved rates of survival compared with those with a cumulative fluid balance .20% (46% vs 68%, P , .01).…”
Section: Neonatal Cardiac Surgerymentioning
confidence: 99%